Quality Assessment and Sensory Evaluation of Syrup Produced from Date Fruits (IPS Journal of Nutrition and Food Science, 2025)
Date syrup offered several important advantages including; wide consumption, being a natural sweetener, rich flavor profile, natural energy source, potential health benefits, versatile culinary uses and it is highly palatable and acceptable in most countries. This study was conducted to investigated the quality assessment and sensory evaluation of syrup produced from date fruits. The date fruits were pitted, soaked, sieved, blended and heated at different temperatures (50 °C, 70 °C, 90 °C, and 100 °C). The proximate, mineral composition, color index, microbial activities as well as physico chemical properties of the date syrup were examined while panelists were assigned to assess the date syrup samples. Colour index showed that L* values of the samples ranged from (5.29±0.00) to (21.27±0.04) also a* values of the samples ranged from (2.73±0.02) to (5.74±1.71) while b* values ranged from (1.14±0.02) to (4.23±0.00).  The results of the proximate composition for the moisture content ranged from (19.34±0.08) % to (61.57±0.02) % which showed that the temperature at which the syrups were heated had significant (p
Keywords: Dates, Quality assessment, Sensory evaluation, Syrup